In vitro antimetastatic activity of Agarwood (Aquilaria crassna) essential oils against pancreatic cancer cells - Dahham, Saad Sabbar; M. Tabana, Yasser; Hassan, Loiy E. Ahmed; Ahamed, Mohamed B. Khadeer; Majid, Aman Shah Abdul; Majid, Amin Malik Shah Abdul (Elsevier, 2016)
Background